Engineering Challenges in Karst - Stevanović, Zoran; Milanović, Petar (Acta Carsologica, 2015)
Anisotropy and heterogeneity of karstified rocks make them the most problematic media for various interventions which are needed in engineering practice. The long history of attempts to adapt karstic nature to human needs started with the utilization of karstic aquifers: tapping large springs, transferring their waters to the long distances, improving minimal flows or capturing fresh water in coastal areas. During the 20th century the number of other challenges such as building dam and reservoirs, and constructing roads and railways, bridges, tunnels, new settlements open a new era in engineering works but also in collecting new knowledge and experience for the karstology and hydrogeology sciences. Today, almost no engineering projects can be implemented without a proper environmental impact assessment, which establishes a better balance between human and ecological needs. Inženirski izzivi v Krasu Anizotropija in heterogenost zakraselih kamnin sta lastnosti, ki povzročata, da so te najbolj problematičen medij za različne posege, ki so potrebni v inženirski praksi. Dolga zgodovina poskusov, da bi prilagodili kraško naravo človekovim potrebam se je začela z izrabo kraških vodonosnikov: izkoriščanje velikih izvirov, prenos vode na dolge razdalje, poviševanje minimalnih pretokov ali zajemanje vode na obalnih območjih. V 20. stoletju je število drugih izzivov, kot so gradnja jezov in rezervoarjev, cest in železnic, mostov, predorov, novih naselij odprla novo obdobje v inženirstvu. Poleg tega je botrovala zbiranju novih krasoslovnih in hidrogeoloških znanj in izkušenj. Danes skoraj noben inženirski projekt ne more biti izveden brez ustrezne presoje vplivov na okolje, kar vzpostavlja boljše ravnotežje med človekovimi in ekološkimi potrebami.